Sustainability models in Zone 3 manufacturing SMEs - Karla Morales; Pamela de Los Ángeles Sánchez Rosero; Christian Alberto López Valencia; Freddy Marco Armijos Arcos (Heritage and Sustainable Development)
In this research, the objective was to determine the optimal financial sustainability model for manufacturing SMEs in zone 3 for the years 2017 - 2020. For the development of the study, 107 medium and small companies that met the requirements of complete information obtained from the Superintendence of Companies, Securities, and Insurance were taken into account. Observation sheets were used to classify the information in the financial statements and allow understanding of their financial situation by applying the solvency prediction models, Z-Altman, Springate, Fulmer, and CA-Score. In the analysis of the financial indicators of manufacturing, SMEs evidenced a strong correlation with their financial sustainability, especially in the year 2019. A comparative analysis of the effectiveness of the four models of financial sustainability is made, for the selection of the most optimal model. In addition, a SWOT analysis was performed in order to identify the strengths and weaknesses of each of them, so, it is revealed that the most optimal and reliable model is Springate, due to its multidimensional approach, adaptability for manufacturing SMEs, simplicity and ability to provide a clear and truthful score. However, it is always advisable to consider the specific context of other models to each company.